Study on Ion Exchange Equilibria Involving I-/SO2-4 and I-/C2O2-4 Uni-Bivalent Ion Exchange Systems - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
Ion exchange resins in iodide form were equilibriated with oxalate and sulphate ion solution of seven different concentrations in the range of 0.010 M to 0.050 M. The equilibrium constant (K) values are calculated in the temperature range of 30 to 45°C. The K value for I-/C2O42- exchange reaction at 30°C was calculated to be 0.260 which was observed to be greater than 0.250 for I-/SO42- exchange at same temperature which was due to the difference in ionic size of sulphate and oxalate ions in solution. The enthalpy of ion exchange reactions was calculated as 12.51 kJ/mole and 14.54 kJ/mole respectively indicating the endothermic ion exchange reaction.